Priority Areas for Increasing the Competitiveness of the Agro-Industrial Complex and Environmental Sustainability - NURMANBETOVA, Arailym; ZHUSSUPOV, Yerzhan; AKIMBEKOVA, Galiya; GRIDNEVA, Yelena; KALIAKPAROVA, Gulnar; KHAN, Yury (Journal of Environmental Management and Tourism; Vol 13 No 1 (2022): JEMT, Volume XIII, Issue 1(57), Spring 2022, 2022)
The article considers the place of agro-industrial complex of Kazakhstan in the national economic complex of the country, which has certain problems that affect the current state.  In the course of the study of the agro-industrial complex the author considered the participation in the formation of the country's GDP, dynamics and structure of gross agricultural output as the main branch of the agro-industrial complex. As a result, the main problems were identified and the priority tasks to solve the problems of management of the agro-industrial complex, based on the target indicators of development of the agro-industrial complex until 2020, in order to further forecast and model the forecast values until 2025 through the dynamics of gross agricultural production of Kazakhstan for 2016-2020, GDP structure by economic activity, the structure of gross agricultural production by industry, profitability of agricultural production, and indicators of import.